Strategi Pembelajaran Adaptif Bagi Peserta Didik Berkebutuhan Khusus - Armitha; Hesti; Helmalia Putri; Ikram; Hasmiati; Nurul Islamiah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
Students with special needs have diverse characteristics, abilities, and learning needs, thus requiring adaptive learning strategies within the inclusive education process. This article aims to analyze various adaptive learning strategies applied to students with special needs and identify the factors influencing their effectiveness. This study employed a literature review method by examining various relevant scientific articles, books, and academic documents published between 2020 and 2025. The review process was conducted through the identification, selection, analysis, and synthesis of literature related to adaptive learning, inclusive education, and students with special needs. The findings indicate that effective adaptive learning strategies include individualized approaches, curriculum differentiation, the use of creative technology-based learning media, and collaboration among teachers, parents, and professional support staff.